Painting as a response to a sense of dislocation in the South African social fabric - Hartzenberg, Randolph Joseph (Michaelis School of Fine Art, 2023)
My proposal was to produce a series of paintings as a response to a sense of dislocation in the South African social fabric. The body of paintings is entitled Domestic Baggage and consists collectively of paintings on canvas and preliminary works entitled The Grids. Thematically consistent, the works and the accompanying research document emphasize the disturbed and marginalized dimensions of fragmented society. A significant frame of reference is the claustrophobic, persistent presence of increasing violence and loss of life arising from the dislocation ethos. lconographically, a strategy of allusion has been adopted, allowing for the interaction of figurative, gestural and material referents. Dependence on overtly illustrative or purely narrative modes of representation has been deferred. An extensive background essay highlights the appropriately identified specifics of the backdrop against which the series of paintings has been developed. A detailed art historical contextualization foregrounds those precedents most pertinent to the formal and conceptual processes informing the Domestic Baggage series.